A Comparison of Diagnostic Value of Anthropometric Indices with Laboratory Criteria for Malnutrition Detection in Chronic Undergoing Hemodialysis Patients - Rahimian, Mohammad; Najafi, Farzaneh; Goharian, Amirreza; Ahmadi, Amir Bahrami (Pakistan Journal of Nutrition, 2006)
Malnutrition is a main problem in undergone hemodialysis patients. Early diagnosis is important and life saving. Using anthropometric indices can help for rapid diagnoses. This study was done to compare anthropometric indices with biochemical parameters. We monitored 60 patients that underwent hemodialysis in Shaheed Rahnemoon hospital. Biochemical parameters and anthropometric indices were measured and compared. On the basis of anthropometric indices, BMI, TSF, MAC; malnutrition prevalence was 18.3%, 21.7%, 28% respectively. By using biochemical parameters include albumin, transferrin, cholesterol, Creatinine and white blood cell Count malnutrition prevalence was 8.3%, 15%, 13%, 10%, 8.3% respectively. Only MAC index has a positive correlation with serum transferrin (r=0.169, p=0.002). Sensitivity and specificity of this test is 40% and 53.33% respectively. Its Negative predictive value is 84.21%. MAC index can be used as a reliable test for rule outing malnutrition in chronic undergone hemodialysis Patients.